(untitled) (Konferensiyalar | Conferences, 2024)
adaptation of first-graders is one of the most multifaceted concepts in pedagogy. Pedagogues of different epochs of society development studied this problem comprehensively. It remains topical even nowadays. The article provides information about the adaptation of children to school, about the period of adaptation child to the conditions of educational institution, to lessons, to the new routine, to procedures, to new people (teachers and classmates). Studying in the first grade - is the most responsible stage in development, since, it is here exact the foundation of morality is laid, the formation of social attitudes, attitudes to oneself, to other people, to society, beliefs are formed. The article draws certain conclusions based on the analysis of scientific literature on the issues of children’s adaptation to school.